2009
DOI: 10.1111/j.1365-2753.2008.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease: appropriateness of therapeutic management and associated factors in the AVENIR study

Abstract: The quality of therapeutic care delivered to CKD patients in nephrology setting was suboptimal when assessed in terms of adherence to guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Some studies showed that management of mineral and bone disorder is very far from optimal, especially as compared with other CKD complications [1][2][3] reflecting a lack of awareness among clinicians about this aspect of care. Others provided evidence that calcium-phosphate metabolism disorders, and particularly excess serum phosphate, are implicated in cardiovascular morbidity and mortality through the formation of vascular calcifications [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that management of mineral and bone disorder is very far from optimal, especially as compared with other CKD complications [1][2][3] reflecting a lack of awareness among clinicians about this aspect of care. Others provided evidence that calcium-phosphate metabolism disorders, and particularly excess serum phosphate, are implicated in cardiovascular morbidity and mortality through the formation of vascular calcifications [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Its methodology was approved by the Ethics Board of the Regional University Hospital and is described in detail elsewhere. 29 All adults with CKD who began dialysis in 1 of the 12 units between January 1, 2005 and December 31, 2006 were identified from the regional ESRD registry (The Renal Epidemiology and Information Network registry) and enrolled in the study. Patients with reversible renal failure and those returning to dialysis after kidney graft failure were not included.…”
Section: Setting Study Design and Sample Selectionmentioning
confidence: 99%
“…This first stage showed that therapeutic practices were suboptimal although the level of adherence to guidelines was somewhat uneven, depending on which of the aspects of CKD therapeutic care was being considered: appropriate management of hypertension/proteinuria was identified as a prominent strength of existing services, whereas inappropriate bone disease management was singled out as a prominent weakness (Table 1). 29 Hence, the aim of the present investigation was to evaluate how the appropriateness of pre-ESRD therapeutic practices affects survival and hospitalization during the first year of RRT, and thereafter to determine whether pre-ESRD therapeutic care CPGs are effective with regard to dialysis morbidity and mortality in a routine care setting.…”
mentioning
confidence: 99%
“…Its main objective was to assess the consequences of therapeutic care delivered to pre-ESRD patients on their quality of life and morbidity/mortality during RRT [6]. The study’s methodology was approved by the Ethics Board of the regional University hospital and is described in detail elsewhere [7]. …”
Section: Methodsmentioning
confidence: 99%